PENGARUH PENGGUNAAN PRE-EMPTIVE SELF DEFENSE IN WAR YANG DIGUNAKAN OLEH NEGARA YANG SEDANG BERKONFLIK UNTUK PENGECULIAN DALAM TANGGUNG JAWAB HUKUM INTERNASIONAL (Studi Kasus : Pasukan Türkiye Menyerang Kaum Khurdis) - Nathaniel Adianta Rim Manurung; Maria Maya Lestari; Zulfikar Jayakusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Self-defense is the right of self-defense granted by the UN Security Councilcontained in Article 51 of the UN Charter. This right can be used by a state inorder to defend itself from an attack from another country. It is well known thatthe development of theories about state self-defense rights has overridden theconcepts of anticipatory self-defense and pre-emtive self-defense that override theprovisions requiring armed attacks before state self-defense rights arise. Article51 of the UN Charter clearly states that the right to self-defense of UN memberstates, individually as well as collectively, only arises